Analysis of Implementation of Maternity Planning and Prevention of Complication (P4K) Program with Stickers in Purwakarta Regency 2017 - Safitri, Yunita Restu; Pujiyanto, Pujiyanto (UI Scholars Hub, 2021)
. Pregnant women are one of the risk groups that should be considered to receive particular attention. Maternal mortality is caused by direct and indirect causes, which generally can be identified in early pregnancy. The Ministry of Health has launched various programs to reduce maternal mortality. At the community level, since 2007, there has been a birth planning and prevention of complications (P4K) program as a screening tool for pregnant women at risk by using stickers. The main point of this program is the active participation of families and communities to care for pregnant women in their environment. Purwakarta Regency, a region with uncomplicated geographical conditions, is supported by Health Human Resources (SDMKes) and Health facilities to do various programs in reducing the number of maternal deaths; one of them is P4K with stickers. In 2017, there were still 21 maternal deaths that should have been identified and referred to the hospital if the program was running well. The study aims to analyze the implementation of the P4K Sticker at the District Level. This research is qualitative research with in-depth interviewing techniques involving 12 informants and related documents, according to the theory of Van Meter and Van Horn policy implementation based on 6 (six) variables. This study found that the standard and policy objectives have not been fully achieved. There is still insufficient funding to support the program optimally. In terms of communication, there still a different understanding between the Health Office and Primary Healthcare Center. Despite there are still constraints on the number of human resources, the program's attitude is supportive. Economic and political situations are good, but social conditions are not supportive. The conclusion is that the program's implementation still has constraints in each variable. Existing program barriers can be overcome by optimizing inter-organizational communication, in this case, the District Health Office with Primary Healthcare Center, to have a common understanding regarding the implementation of Sticker P4K.